Tax Incentives for the Mineral Mining Sector in Indonesia as an Effort to Increase Investment - Selvi Selvi; Notika Rahmi; Idar Rachmatulloh; Alief Ramdan (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Tax incentives are a popular policy among developing countries because these countries have a greater investment risk than developed countries, especially regarding poor infrastructure and the ineffectiveness of existing institutions in these developing countries. The purpose of this study is to analyze whether the application of tax incentives in the mineral mining sector can increase investment interest in Indonesia. This research is descriptive research with a qualitative approach. The results of the study show that the implementation of tax incentives is not a strong consideration for potential investors in investing in the mineral mining sector in Indonesia. In fact, there are other factors that need to be improved in order to increase investor interest, namely policy factors related to administrative uncertainty, interpretation and enforcement of existing regulations, environmental regulations, duplication and inconsistency of regulations, uncertainty regarding disputed land claims and protected areas, infrastructure (including access to roads, ports, availability of electricity and other supporting facilities), socio-economic agreements, political stability, labor issues, geologicalÂ databases, and security.